El liderazgo en la gestión administrativa del Gobierno Autónomo Descentralizado Municipal del cantón Gonzanamá, periodo 2020-2021 - Yaguana Carrión, Gloria Ayde (2022)
Leadership and administrative management are two variables of great relevance in the public sector today, since they are closely related to each other. Since the main purpose of leaders is to successfully achieve the results, objectives and goals proposed by the institutions, through the various management indicators that are reflected in the operational plans duly approved according to their nature and area, therefore, in order to respond to what it has been mentioned, it is necessary to have a type of leadership that allows to demonstrate a solid administrative management. Thus, the objective of this research is to identify the type of leadership implemented by the authorities of the municipality of the canton of Gonzanamá and its relationship with the administrative management during the period 2020-2021. Therefore, in order to achieve the main purpose, a mixed approach and a non-experimental transactional correlational-causal design was applied, and its scope was synthetic-analytical and inductive-deductive. Finally, a Likert scale survey was used, as well as documentary analysis cards and the Chi-Square statistical method, which with a P-value of 0.00 rejected the H0 and led to the conclusion that leadership styles do have a relationship with the administrative management of the Decentralized Autonomous Government (GAD) of Canton Gonzanamá.